2005
DOI: 10.1111/j.1469-7610.2005.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical decision making: a selective review for child psychiatrists and psychologists

Abstract: Physicians, including child and adolescent psychiatrists, show variability and inaccuracies in diagnosis and treatment of their patients and do not routinely implement evidenced-based medical and psychiatric treatments in the community. We believe that it is necessary to characterize the decision-making processes of child and adolescent psychiatrists using theories and methods from cognitive and social sciences in order to design effective interventions to improve practice and education. This paper selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 92 publications
2
69
0
3
Order By: Relevance
“…Although the vignette did not directly reflect symptoms of these mood disorders, irritability is a valid symptom criterion for depression, so this is not entirely surprising. This variability in diagnostic assignment is consistent with other studies documenting a lack of reliability and consistency in mental health diagnoses for children across reporters and/or diagnostic assessment methods [33,42,43].…”
Section: Physician Decision-making For Children With Disruptive Behavsupporting
confidence: 76%
“…Although the vignette did not directly reflect symptoms of these mood disorders, irritability is a valid symptom criterion for depression, so this is not entirely surprising. This variability in diagnostic assignment is consistent with other studies documenting a lack of reliability and consistency in mental health diagnoses for children across reporters and/or diagnostic assessment methods [33,42,43].…”
Section: Physician Decision-making For Children With Disruptive Behavsupporting
confidence: 76%
“…There have been considerable efforts to make explicit the processes involved in clinical reasoning (e.g., Borleffs, Custers, van Gijn, & ten Cate, 2003;Elstein, Shulman, & Sprafka, 1978;Falvey, Bray, & Hebert, 2005;Schmidt, Norman, & Boshuizen, 1990), and to apply models of decisionmaking to clinical reasoning (e.g., Galanter & Patel, 2005;Ward, Vertue, & Haig, 1999).…”
mentioning
confidence: 99%
“…Research in other fields such as medicine and psychiatry showed that structured decision making can increase the reliability of treatment decisions (Galanter & Patel, 2005;Garb, 2005). In (mental) health care, introducing a (computerized) decision support system has improved practitioners' performance, for example, disease management, drug dosing, or transparency of the decisions (Garg et al, 2005;Witteman & Kunst, 1999).…”
Section: Decision Support For Intervention Plansmentioning
confidence: 99%